New serological markers in medical mycology: (1,3) –B-D-glucan and Aspergillus galactomannan - Ostrosky Zeichner, Luis (2012)
Invasive fungal infections present a great challenge in modern medicine. The recent development of serologic markers represents a clear advance in the field. Two serological tests have been developed: (1,3)-β-D glucan and Aspergillus galactomannan. This review discusses highlights of both tests.